Pelatihan Integrasi Media Pembelajaran Dalam Pelaksanaan Pembelajaran Guru Sekolah Dasar Kecamatan Banawa - Anjar Kusuma Dewi; Darmawan; Mashuri; Munawarrah Sipanawa (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2023)
The Community Service Program (PKM) aims to enhance the competence of elementary school teachers in the Teacher Working Group (KKG) Gugus 3 Dian Pertiwi, Banawa, using interactive learning platforms Quizizz and Kahoot. Involving five lecturers from the English Education program and two students from the Faculty of Teacher Training and Education at Tadulako University, this training was attended by 30 teachers. The activity introduces and improves teachers' skills in integrating educational technology into the Free Learning curriculum. Training methods include presentations, demonstrations, hands-on practice, and Q&A sessions, allowing teachers to understand, design, and implement interactive quizzes in their teaching. Evaluation and feedback indicate a significant improvement in teachers' understanding and confidence in using both platforms. The training also facilitates collaboration among teachers and the development of individual action plans for implementation in the classroom. The results show that the training successfully enhances teachers' ability to integrate interactive educational technology, which is expected to impact student engagement and understanding in the learning process positively